2017
DOI: 10.3892/etm.2017.5406
|View full text |Cite
|
Sign up to set email alerts
|

Maternal natural killer cell immunoglobulin receptor genes and human leukocyte antigen-C ligands influence recurrent spontaneous abortion in the Han Chinese population

Abstract: The underlying mechanism of recurrent spontaneous abortion (RSA) has remained elusive for many years. Several previous studies have suggested that the killer cell immunoglobulin receptor (KIR) gene family is associated with RSA, however, it is not clear exactly how. The present study detected KIR and human leukocyte antigen-C (HLA-C) genes in 110 Han Chinese women with unexplained RSA and 105 Han Chinese healthy females. The aim of the present study was to determine if certain genotypes were more susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 74 publications
0
12
0
1
Order By: Relevance
“…These studies also confirmed that KIR and HLA class I combinatorial diversity is an important factor in pregnancy syndromes, infectious disease, blood cancers and transplantation outcome in the Han. They also uncovered both similarities and differences from the specific disease associations observed in Europeans (Bao et al 2016;Jiang et al 2013;Long et al 2015;Shen et al 2016;Su et al 2018). To investigate these findings, we have examined how demographic and evolutionary processes have shaped combinatorial diversity of HLA class I and KIR in the Chinese Southern Han.…”
Section: Introductionmentioning
confidence: 83%
“…These studies also confirmed that KIR and HLA class I combinatorial diversity is an important factor in pregnancy syndromes, infectious disease, blood cancers and transplantation outcome in the Han. They also uncovered both similarities and differences from the specific disease associations observed in Europeans (Bao et al 2016;Jiang et al 2013;Long et al 2015;Shen et al 2016;Su et al 2018). To investigate these findings, we have examined how demographic and evolutionary processes have shaped combinatorial diversity of HLA class I and KIR in the Chinese Southern Han.…”
Section: Introductionmentioning
confidence: 83%
“…The killer cell immunoglobulin-like receptors (KIR) are a family of inhibitory or activating cell surface receptors expressed on natural killer cells and some T lymphocyte subpopulations [47]. Natural killer cells are granular cells that account for 10-15% of lymphocytes in the blood and serve a vital role in immune regulations and defense [48,49]. Prior to implantation, natural uterine killer cells accumulate and represent the majority of decidua lymphocytes in the endometrium during early pregnancy in humans [48,50].…”
Section: Positional Candidate Genesmentioning
confidence: 99%
“…Natural killer cells are granular cells that account for 10-15% of lymphocytes in the blood and serve a vital role in immune regulations and defense [48,49]. Prior to implantation, natural uterine killer cells accumulate and represent the majority of decidua lymphocytes in the endometrium during early pregnancy in humans [48,50]. Multiple studies have identified associations with recurrent SA and killer cell immunoglobulin-like receptor proteins in humans [51][52][53][54][55][56][57][58][59][60][61][62], although some studies have refuted these associations [63,64].…”
Section: Positional Candidate Genesmentioning
confidence: 99%
“…2016 ; Shen et al. 2016 ; Su et al 2018 ). To investigate these findings, we have examined how demographic and evolutionary processes have shaped combinatorial diversity of HLA class I and KIR in the Chinese Southern Han (CHS).…”
Section: Introductionmentioning
confidence: 99%